Lithium ion solid state battery
By setting the container department and forming a solid electrolyte film on the surface of the lithium negative pole tablet, the problem of poor interface performance between lithium negative pole tablets and solid electrolytes is solved, and higher interface stability and battery cycle stability are achieved.
Patent Information
- Application Number
- CN202422950308.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2034-12-02
AI Technical Summary
The interface performance between the lithium negative electrode sheet and the solid electrolyte is poor, which is prone to cause interface reactions and battery short circuits.
Set the capacity department on the lithium negative pole tablet, and set the solid electrolyte layer between the positive pole film and the lithium negative pole tablet. Among them, the solid electrolyte layer is set in at least part of the capacity department, and a thin solid state surface is formed on the surface of the lithium negative pole tablet. Electrolytic film.
Effectively avoid the direct contact between the solid electrolyte layer and the lithium -negative polar chip, reduce the interface side -by -side reaction, improve the stability of the interface, inhibit the growth of lithium branches, and avoid short circuit of battery.
Smart Images

Figure CN222422031U_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a lithium-ion solid-state battery. Background Art
[0002] Compared with commercial lithium-ion batteries based on liquid electrolytes, all-solid-state lithium batteries have higher energy density and excellent safety performance, and are considered to be one of the most promising energy storage devices. Lithium negative electrode sheets have the advantages of low potential and high theoretical capacity. When used with high-voltage and high-capacity positive electrode sheets, lithium negative electrode sheet lithium-ion solid-state batteries can obtain higher storage capacity. Lithium negative electrode sheet lithium-ion solid-state batteries have become a research hotspot recently.
[0003] However, due to the poor interface performance between the solid electrolyte and the lithium negative electrode in lithium-ion solid-state batteries, if there is unstable contact between the solid electrolyte and the lithium negative electrode, even a tiny crack may trigger a violent interface reaction, causing the interface performance to degrade rapidly, and the resulting lithium dendrites may penetrate the solid electrolyte membrane and cause the battery to short-circuit. Therefore, the interface problem between the lithium negative electrode and the solid electrolyte has seriously restricted the development of solid-state lithium metal batteries. Utility Model Content
[0004] Based on this, it is necessary to provide a lithium-ion solid-state battery to solve the interface problem between the lithium negative electrode plate and the solid electrolyte to avoid battery short circuit.
[0005] The specific solution of this application to solve the above technical problems is as follows:
[0006] A lithium-ion solid-state battery comprises a positive electrode sheet, a lithium negative electrode sheet, and a solid electrolyte layer disposed between the positive electrode sheet and the lithium negative electrode sheet, wherein a receiving portion is disposed on the lithium negative electrode sheet, and the solid electrolyte layer is at least partially disposed in the receiving portion; the solid electrolyte layer comprises a binder base layer; wherein the cross section of the receiving portion is an arc, and the arc satisfies L=απr / 180, and α≤100°, r≤T, wherein L is the arc length, α is the center angle corresponding to the arc, r is the radius of the circle where the arc is located, and T is the thickness of the lithium negative electrode sheet;
[0007] A solid electrolyte film is provided on the inner wall of the receiving portion and / or the surface of the lithium negative electrode plate;
[0008] The thickness of the solid electrolyte film is 1nm~100nm;
[0009] The solid electrolyte film is a LiF film, a Li2O film, a LiPON film or a LiNiO2 film.
[0010] In some embodiments, the opening diameter of the accommodation portion is d, the distance between any adjacent accommodation portions is D, and d / 2≤D≤2d.
[0011] In some embodiments, the angle β between the tangent line at the endpoint of the arc and the plane of the lithium negative electrode sheet is 5° to 45°.
[0012] The present application can effectively avoid direct contact between the solid electrolyte layer and the lithium negative electrode sheet by setting a thin solid electrolyte film between the lithium negative electrode sheet and the solid electrolyte layer, reduce interface side reactions, and improve interface stability. At the same time, a layer of solid electrolyte film is formed on the surface of the lithium negative electrode sheet, which can effectively inhibit the growth of dendrites of the lithium negative electrode sheet and prevent lithium dendrites from penetrating the solid electrolyte layer and causing a battery short circuit.
[0013] In some embodiments, the inner wall of the receiving portion and / or the surface of the lithium negative electrode sheet is a rough surface.
[0014] In the present application, by setting the inner wall of the accommodation portion and / or the surface of the lithium negative electrode plate to a rough surface, a suitable roughness helps to improve the bonding force between the film layers.
[0015] In some embodiments, a protruding structure is formed on the inner wall of the receiving portion and / or the surface of the lithium negative electrode sheet, and the protruding structure is at least partially disposed in the solid electrolyte layer.
[0016] In some embodiments, the thickness of the lithium negative electrode plate is 5 um to 300 um.
[0017] In some embodiments, the thickness of the solid electrolyte layer is 5 um to 100 um.
[0018] In some embodiments, a modified layer is disposed on a side of the solid electrolyte layer close to the lithium negative electrode plate, and the modified layer of the solid electrolyte layer is connected to the lithium negative electrode plate.
[0019] Compared with the traditional technology, the beneficial effects of this application are as follows:
[0020] The present application provides a receiving portion on the lithium negative electrode sheet, and the solid electrolyte layer is at least partially provided in the receiving portion, thereby increasing the contact area between the solid electrolyte layer and the lithium negative electrode sheet. In the present application, the cross-sectional arc of the receiving portion satisfies L=απr / 180, and α≤100°, r≤T, which is beneficial for the solid electrolyte particles in the solid electrolyte layer to enter the receiving portion more smoothly when the solid electrolyte layer and the lithium negative electrode sheet are pressed together, and it is also easier to fill the receiving portion with solid electrolyte particles, thereby effectively increasing the contact and bonding area between the solid electrolyte layer and the lithium negative electrode sheet, so that the solid electrolyte layer and the lithium negative electrode sheet are in sufficient close contact, thereby improving the bonding strength between the solid electrolyte layer and the lithium negative electrode sheet, and improving the interface contact performance between the lithium negative electrode sheet and the solid electrolyte layer.
[0021] At the same time, the active groups in the binder base layer in the solid electrolyte layer can combine with the lithium metal in the lithium negative electrode to form a more stable contact interface. The excellent interface performance between the lithium negative electrode and the solid electrolyte layer also improves the cycle stability of lithium-ion solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0023] In order to more completely understand the present application and its beneficial effects, the following description will be given in conjunction with the accompanying drawings. In the following description, the same reference numerals represent the same parts.
[0024] Figure 1 Schematic diagram of the structure of a lithium-ion solid-state battery in one embodiment of the present application.
[0025] Figure 2 This is a schematic diagram of the structure of a lithium negative electrode plate in one embodiment of the present application (without a solid electrolyte film).
[0026] Figure 3 This is a schematic diagram of the enlarged structure of a partial area of the lithium negative electrode plate in one embodiment of the present application (without a solid electrolyte film).
[0027] Figure 4 Schematic diagram of the cross-sectional structure of a lithium negative electrode plate in one embodiment of the present application (with a protrusion mechanism).
[0028] Figure 5 This is a schematic diagram of the enlarged structure of a partial area of a lithium negative electrode plate in one embodiment of the present application (provided with a solid electrolyte film).
[0029] Figure 6 Schematic diagram of the cross-sectional structure of a lithium negative electrode plate in one embodiment of the present application (provided with a solid electrolyte film).
[0030] Figure 7 Schematic diagram of the cross-sectional structure of a lithium negative electrode plate in one embodiment of the present application (provided with a solid electrolyte film).
[0031] Description of Reference Numerals
[0032] 1. Positive electrode sheet; 2. Lithium negative electrode sheet; 3. Solid electrolyte layer;
[0033] 21. Accommodating portion; 211. Solid electrolyte film. DETAILED DESCRIPTION
[0034] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0035] In the description of the present application, it should be understood that if the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. appear, the orientation or position relationship indicated by these terms is based on the orientation or position relationship shown in the accompanying drawings, which is only for the convenience of describing the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.
[0036] In addition, if the terms "first" or "second" appear, these terms are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, if the term "plurality" appears, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0037] In this application, unless otherwise clearly specified and limited, if the terms "installed", "connected", "connected", "fixed" and the like appear, these terms should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integrated connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0039] It should be noted that if an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be an intermediate element. If an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.
[0040] In traditional lithium-ion solid-state batteries, the interface contact between the solid electrolyte layer 3 and the lithium negative electrode plate is poor, and the unstable contact between the interfaces easily causes interface reactions, resulting in a rapid decrease in interface performance, which in turn affects the electrochemical performance of the lithium-ion solid-state battery. Therefore, how to provide a lithium-ion solid-state battery with excellent interface performance has become a technical problem that needs to be solved urgently.
[0041] like Figures 1 to 7 As shown, the present application provides a lithium-ion solid-state battery. The lithium-ion solid-state battery includes a positive electrode plate 1, a lithium negative electrode plate 2, and a solid electrolyte layer 3 disposed between the positive electrode plate 1 and the lithium negative electrode plate 2. Among them, a receiving portion 21 is provided on the lithium negative electrode plate 2, and the solid electrolyte layer 3 is at least partially disposed in the receiving portion 21; the solid electrolyte layer 3 includes a binder base layer. Among them, the cross-section of the receiving portion 21 is an arc, and the arc satisfies L=απr / 180, and α≤100°, r≤T, wherein L is the arc length of the arc, α is the size of the central angle corresponding to the arc, r is the radius of the circle where the arc is located, and T is the thickness of the lithium negative electrode plate 2.
[0042] In some embodiments, the inner wall of the receiving portion 21 may be a spherical surface, but is not limited thereto.
[0043] In some specific embodiments, the receiving portion 21 may be formed on the surface of the lithium negative electrode plate 2 by pulse laser etching or other techniques.
[0044] In the present application, the receiving portion 21 is provided on the lithium negative electrode sheet, and the solid electrolyte layer 3 is at least partially provided in the receiving portion 21, so that the solid electrolyte layer 3 and the lithium negative electrode sheet 2 are in full close contact, thereby increasing the contact area between the solid electrolyte layer 3 and the lithium negative electrode sheet 2. In the present application, the cross-sectional arc of the receiving portion 21 satisfies L=απr / 180, and α≤100°, r≤T, which is conducive to the solid electrolyte particles in the solid electrolyte layer 3 entering the receiving portion 21 more smoothly when the solid electrolyte layer 3 and the lithium negative electrode sheet 2 are pressed together, and it is also easier to fill the receiving portion 21 with solid electrolyte particles, thereby effectively increasing the contact and bonding area between the solid electrolyte layer 3 and the lithium negative electrode sheet 2, so that the solid electrolyte layer 3 and the lithium negative electrode sheet 2 are in full close contact, the bonding strength between the solid electrolyte layer 3 and the lithium negative electrode sheet 2 is increased, and the interface contact performance between the lithium negative electrode sheet 2 and the solid electrolyte layer 3 is improved.
[0045] At the same time, the active groups in the binder base layer in the solid electrolyte layer 3 can combine with the lithium metal in the lithium negative electrode plate 2 to form a more stable contact interface. The excellent interface performance between the lithium negative electrode plate 2 and the solid electrolyte layer 3 also improves the cycle stability of the lithium-ion solid-state battery.
[0046] In some embodiments, the opening shape of the accommodation portion 21 is circular, the opening diameter of the accommodation portion 21 is d, the distance between any adjacent accommodation portions is D, and d / 2≤D≤2d.
[0047] In the above embodiment, the opening diameter d of the accommodating portion 21 and the distance D between any adjacent accommodating portions 21 satisfy d / 2≤D≤2d, so that the lithium negative electrode plate 2 can maintain sufficient mechanical strength and increase as many accommodating portions 21 as possible, that is, the arrangement of the lithium negative electrode plate 2 can maintain sufficient mechanical strength while maximizing the bonding area between the solid electrolyte layer 3 and the lithium negative electrode plate 2 to meet the actual use conditions of the lithium negative electrode plate 2.
[0048] It should be noted that the shape of the opening of the accommodating portion 21 is not particularly limited in the present application. For example, the shape of the opening of the accommodating portion 21 may be an ellipse or other shapes.
[0049] In some embodiments, the angle β between the tangent line at the endpoint of the arc and the plane of the lithium negative electrode plate 2 is 5° to 45°.
[0050] In some of the embodiments, a solid electrolyte film 211 is provided on the inner wall of the accommodating portion 21 and / or the surface of the lithium negative electrode plate 2, and the solid electrolyte film 211 is at least one of a LiF film, a Li2O film, a LiPON film and a LiNiO2 film.
[0051] In some of the embodiments, the solid electrolyte film 211 is prepared on the inner wall of the receiving portion 21 and / or the surface of the lithium negative electrode plate 2 by magnetron sputtering.
[0052] In some embodiments, the thickness of the solid electrolyte film 211 is 1nm~100nm, including but not limited to 1nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, and 100nm.
[0053] The present application sets a thin solid electrolyte film 211 between the lithium negative electrode plate 2 and the solid electrolyte layer 3. The solid electrolyte film 211 is at least one of a LiF film, a Li2O film, a LiPON film and a LiNiO2 film, and artificially constructs an interface SEI film, which can effectively improve the transmission efficiency of active lithium between the solid electrolyte layer 3 and the lithium negative electrode plate 2, reduce interface side reactions, and improve interface stability. At the same time, a layer of solid electrolyte film 211 is formed on the surface of the lithium negative electrode plate 2, which is conducive to the uniform deposition of active lithium, and can effectively inhibit the growth of dendrites of the lithium negative electrode plate 2, and prevent lithium dendrites from penetrating the solid electrolyte layer 3, resulting in a battery short circuit.
[0054] In some embodiments, the inner wall of the receiving portion 21 and / or the surface of the lithium negative electrode sheet 2 is a rough surface.
[0055] In some of the embodiments, chemical etching or physical etching is used to form a rough surface on the inner wall of the receiving portion 21 and / or the surface of the lithium negative electrode plate 2 .
[0056] In the present application, by setting the inner wall of the accommodation portion 21 and / or the surface of the lithium negative electrode plate 2 to a rough surface, a suitable roughness helps to improve the bonding force between the film layers.
[0057] In some embodiments, the lithium negative electrode plate 2 is a lithium metal negative electrode plate, a lithium alloy negative electrode plate or a lithium metal composite negative electrode plate.
[0058] Among them, the lithium alloy negative electrode plate refers to an alloy of lithium metal and other metal or non-metal elements, and the other metal or non-metal elements are at least one of Na, K, Mg, Ca, Ba, Ni, Zn, Al, In, Sn, Sb, Pb, Ag, B, Si and C.
[0059] The lithium metal composite negative electrode plate refers to a composite electrode plate obtained by compounding a lithium metal foil with a binder layer, a lithium metal foil with a binder and a functional layer mixed with a conductive metal, conductive carbon, oxide, sulfide, nitride, carbide, fluoride, solid electrolyte, etc.
[0060] In some embodiments, the binder includes but is not limited to at least one of polytetrafluoroethylene, polyvinylidene fluoride, polypropylene, polyethylene, styrene-butadiene rubber, nitrile rubber, sodium hydroxymethyl cellulose, polyacrylic acid, polyacrylonitrile, sodium alginate, polyaniline, polypyrrole, polyethylene oxide, polyvinyl pyrrolidone, polyethylene carbonate, polypropylene carbonate, and polytrimethylene carbonate.
[0061] In some embodiments, the conductive metal is a lithiophilic metal or a lithiophilic semimetal, including one or more of zinc powder, tin powder, aluminum powder, silver powder, gold powder, silicon powder, black phosphorus, etc.
[0062] In some embodiments, the conductive carbon includes one or more of graphite, carbon black, carbon fiber, carbon nanotube, graphene, fullerene, and heteroatom-doped carbon.
[0063] In some embodiments, the oxide includes one or more of magnesium oxide, aluminum oxide, silicon dioxide, silicon monoxide, calcium oxide, titanium dioxide, vanadium oxide, manganese oxide, iron oxide, tin oxide, copper oxide, zinc oxide, molybdenum oxide, niobium oxide, tungsten oxide, bismuth oxide, graphene oxide, barium titanate, and sodium niobate.
[0064] In some embodiments, the sulfide includes one or more of iron sulfide, cobalt sulfide, nickel sulfide, manganese sulfide, molybdenum sulfide, cadmium sulfide, tin sulfide, bismuth sulfide, and tungsten sulfide.
[0065] In some embodiments, the nitride includes one or more of lithium nitride, boron nitride, aluminum nitride, silicon nitride, calcium nitride, titanium nitride, magnesium nitride, manganese nitride, tungsten nitride, zirconium nitride, molybdenum nitride, vanadium nitride, chromium nitride, zirconium nitride, niobium nitride, tantalum nitride, and tungsten nitride.
[0066] In some embodiments, the carbide includes one or more of boron carbide, silicon carbide, calcium carbide, chromium carbide, tantalum carbide, titanium carbide, and tungsten carbide.
[0067] In some embodiments, the fluoride includes one or more of iron fluoride, lithium fluoride, and calcium fluoride.
[0068] In some embodiments, a protruding structure is formed on the inner wall of the receiving portion 21 and / or the surface of the lithium negative electrode plate 2 , and the protruding structure is at least partially disposed in the solid electrolyte layer 3 .
[0069] In some embodiments, the solid electrolyte layer 3 includes polymer solid electrolyte particles, and the polymer solid electrolyte particles are filled in a binder base layer.
[0070] It is understandable that in the present application, there is no particular limitation on the type of polymer solid electrolyte. Under the premise of being consistent with the overall inventive concept of the present application, all existing types of polymer solid electrolytes can be applied to the present application.
[0071] The following is merely an example, and the components of the polymer solid electrolyte particles may include one or more polymer materials selected from the group consisting of polyethylene glycol, polyethylene oxide (PEO), poly(p-phenylene ether) (PPO), poly(methyl methacrylate) (PMMA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP), polyvinyl chloride (PVC), and combinations thereof.
[0072] It can be understood that in the present application, the arc satisfies L=απr / 180, and α≤100°, r≤T, which is conducive to the polymer solid electrolyte particles in the polymer solid electrolyte layer 3 being able to enter the receiving portion 21 more smoothly when the polymer solid electrolyte layer 3 is pressed with the lithium negative electrode plate 2, and it is also easier to fill the receiving portion 21 with polymer solid electrolyte particles, thereby effectively increasing the contact and bonding area between the polymer solid electrolyte layer 3 and the lithium negative electrode plate 2. At the same time, the active groups of the polymer solid electrolyte particles can be combined with the lithium metal in the lithium negative electrode plate 2 to form a more stable contact interface.
[0073] In some embodiments, the solid electrolyte layer 3 includes a solid electrolyte that is stable to metallic lithium or has no sustained side reactions.
[0074] In some embodiments, the solid electrolyte includes one or more of lithium carbonate, lithium lanthanum zirconium oxide, lithium phosphorus oxynitride, antiperovskite type, and argyrodite type.
[0075] In some embodiments, the thickness of the lithium negative electrode plate 2 is 5um~300um, including but not limited to 5um, 50um, 100um, 150um, 200um, 250um, and 300um.
[0076] In some preferred embodiments, the thickness of the lithium negative electrode plate 2 is 10um to 50um;
[0077] Further, in some embodiments, the opening diameter of the accommodation portion 21 is 10nm~1000nm, including but not limited to 10nm, 100nm, 150nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, and 1000m.
[0078] Further, in some embodiments, the depth of the accommodation portion 21 is 0.1um~3um, including but not limited to 0.1um, 0.15um, 0.2um, 0.25um, and 0.3um.
[0079] In some embodiments, the thickness of the solid electrolyte layer 3 is 5um~100um, including but not limited to 5um, 10um, 20um, 30um, 40um, 50um, 50um, 60um, 70um, 80um, 90um, and 100um.
[0080] In some embodiments, a modified layer is provided on one side of the solid electrolyte layer 3 close to the lithium negative electrode plate 2, and the modified layer of the solid electrolyte layer 3 is connected to the lithium negative electrode plate 2. The modified layer is a fluorinated modified layer, an amidated modified layer, an etherified modified layer or a carboxyl modified layer.
[0081] In some of the embodiments, a modified layer can be provided on the solid electrolyte layer 3 by plasma treatment of a relevant active group gas source, CVD / plasma / evaporation and other methods for anion exchange, or by coating the surface of the solid electrolyte layer 3 with an oligomer having the above-mentioned active groups.
[0082] By setting a fluorination modification layer, an amidation modification layer, an etherification modification layer or a carboxylation modification layer on the surface of the solid electrolyte layer 3 close to the lithium negative electrode plate 2, the active groups such as fluorine, amide group, ether group, carboxyl group, etc. on the surface of the solid electrolyte layer 3 can be increased. On the one hand, these active groups can promote the dissociation and conduction of lithium ions, and further improve the transmission efficiency of lithium ions at the interface between the solid electrolyte layer 3 and the lithium negative electrode plate 2. On the other hand, in addition to the active groups possessed by the binder and the polymer solid electrolyte particles themselves, these groups can further strengthen the reaction and combination with the lithium metal in the lithium negative electrode plate 2, thereby improving the bonding strength between the solid electrolyte layer 3 and the lithium negative electrode plate 2.
[0083] In some of the embodiments, the solid electrolyte layer 3 further includes inorganic solid electrolyte particles, and the inorganic solid electrolyte particles are dispersed in the binder base layer in the solid electrolyte layer 3 .
[0084] In some embodiments, the inorganic solid electrolyte particles are halide solid electrolyte particles.
[0085] Halide solid electrolytes have excellent room-temperature ionic conductivity. However, halide solid electrolytes have a relatively high reduction potential and are unstable with respect to lithium, so their compatibility with lithium anodes is poor. By dispersing halide solid electrolyte particles in the solid electrolyte layer 3, direct contact between the halide solid electrolyte and the lithium anode is avoided, improving the compatibility between the halide electrolyte and the lithium anode.
[0086] In some of these embodiments, the halide solid electrolyte includes Li2CdCl4, Li2MgCl4, Li2CdI4, Li2ZnI4, Li3OCl, LiI, Li5ZnI4, Li3OCl 1-x Br x (where 0 < x < 1) and combinations thereof.
[0087] However, without limitation, the inorganic solid electrolyte may also include one or more of oxide solid electrolytes, sulfide solid electrolytes, hydride solid electrolytes, boride solid electrolytes, and nitride solid electrolytes.
[0088] Specifically, the oxide solid electrolyte may include one or more garnet ceramics, LISICON-type oxides, NASICON-type oxides, and perovskite-type ceramics. For example: one or more garnet ceramics may be selected from the group consisting of: Li 6.5 La3Zr 1.75 Te 0.25 O 12 、Li7La3Zr2O 12 、Li 6.2 Ga 0.3 La 2.95 Rb 0.05 Zr2O 12 、Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 、Li 6.25 Al 0.25 La3Zr2O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 and combinations thereof. One or more LISICON-type oxides may be selected from the group consisting of: Li14Zn(GeO4)4, Li 3+x (P 1-x Si x)O4 (where 0 < x < 1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1) and combinations thereof.
[0089] One or more NASICON-type oxides can be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example: In certain variants, one or more NASICON-type oxides can be selected from the group consisting of: Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1+x Al x Ti 2-x (PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li 1+x Y x Zr 2-x (PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li 1.3 Al 0.3 Ti 1. 7(PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, and combinations thereof.
[0090] One or more perovskite-type ceramics can be selected from the group consisting of: Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1. 3Ta 1.7 O9, Li 2x-y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25) and combinations thereof.
[0091] The sulfide solid electrolyte consists of sulfide solid electrolyte particles and can include one or more sulfide-based materials selected from the group consisting of: Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge, and Sn and 0 ≤ x ≤ 2), Li 3.4 Si0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , Li 9.6 P3S 12 、Li7P3S 11 、Li9P3S9O3、Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 、Li(Ge 0.5 Sn 0.5 )P2S 12 , Li 10 GeP2S 12 (LGPS), Li6PS5X (where X is Cl, Br or I), Li7P2S8I, Li 10.35 Ge 1.35 P 1.65 S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 10 SnP2S 12 , Li 10 SiP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 、(1-x)P2S 5-x Li2S (wherein 0.5≤x≤0.7) and combinations thereof.
[0092] The hydride solid electrolyte is composed of hydride solid electrolyte particles, and the hydride-based particles may include one or more hydride-based materials selected from the group consisting of: Li3AlH6, LiBH4, LiBH4-Li X (wherein X is one of Cl, Br and I), LiNH2, Li2NH, LiBH4-LiNH2 and combinations thereof.
[0093] The boride solid electrolyte is composed of borate solid electrolyte particles, including one or more borate-based materials from the group consisting of Li2B4O7, Li2O-(B2O3)-(P2O5), and combinations thereof.
[0094] The nitride solid electrolyte is composed of nitride solid electrolyte particles, including Li3N, Li7PN4, LiSi2N3, LiPON and combinations thereof.
[0095] In some of the embodiments, the mass ratio of the inorganic solid electrolyte particles to the solid electrolyte layer 3 is 5% to 30%.
[0096] In some of the embodiments, the solid electrolyte layer 3 further includes lithium salt particles, and the lithium salt particles are dispersed in a binder base layer in the solid electrolyte layer 3 .
[0097] Specifically, the lithium salt particles are selected from particles of lithium hexafluorophosphate, lithium perchlorate, lithium tetrachloroaluminate, lithium iodide, lithium bromide, lithium thiocyanate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium tetraphenylborate, lithium bis(oxalate)borate, lithium tetrafluorooxalatophosphate, lithium nitrate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), and the like.
[0098] In the present application, there is no particular limitation on the positive electrode sheet 1. As long as it can function as the positive electrode sheet 1 of the solid battery, it is acceptable as long as it conforms to the overall inventive concept of the present application. The following is merely an example, the positive electrode sheet 1 includes a positive electrode current collector and an active layer disposed on at least one surface of the positive electrode current collector, and the active layer includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the active layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0099] In some embodiments, the positive electrode current collector is not particularly limited, as long as it has conductivity and does not cause chemical changes in the battery. The positive electrode current collector can be a metal foil or a composite current collector (a metal material can be arranged on a polymer substrate to form a composite current collector). Specifically, stainless steel, aluminum, nickel, titanium, or a metal current collector with a surface treated with carbon or other substances can be used. As an example, the positive electrode current collector can be selected from aluminum foil, carbon-coated aluminum foil, or stainless steel sheet.
[0100] In some embodiments, the positive electrode active material includes but is not limited to a lithium iron phosphate positive electrode, a lithium manganate positive electrode, a lithium iron manganese phosphate positive electrode, and a ternary positive electrode.
[0101] In some embodiments, the ternary positive electrode includes: LiCoO2, LiNiO2, LiFePO4, Li3V2(PO4)3, Li3V3(PO4)3, LiVPO4F, Li2CuO2, Li5FeO4, LiCo x Ni 1-x O2、LiCo x Ni 1-x-y Al y O2, LiMn2O4, Li 1+a L 1-b- c M d N e O2、LiFe f Mn g Q h O4, metal sulfides and metal oxides, wherein 0≤x≤1, 0≤y≤1, -0.1≤a≤0.2, 0≤b≤1, 0≤c≤1, 0≤b+c≤1, 0≤d≤1, 0≤e≤1, L, M, N are at least one selected from Li, Co, Mn, Ni, Fe, Al, Mg, Ga, Ti, Cr, Cu, Zn, Mo, F, I, S and B, 0≤f≤1, 0≤g≤1, 0≤h≤1, f+g+h=1, and Q is at least one selected from Al, Mg, Ga, Cr, Co, Ni, Cu, Zn and Mo.
[0102] In some embodiments, the positive electrode conductive agent includes but is not limited to acetylene black, Ketjen black, super-P and carbon fiber.
[0103] In some embodiments, the positive electrode binder includes, but is not limited to, polyvinylidene fluoride PVDF, polytetrafluoroethylene PTFE, styrene-butadiene rubber SBR, sodium alginate SA, polyvinyl alcohol PCN, polyacrylic acid PAA, polyacrylonitrile PAN, and the like.
[0104] In the present application, there is no particular limitation on the lithium negative electrode sheet 2. As long as it can function as a lithium negative electrode sheet 2 of a solid battery, it is acceptable as long as it conforms to the overall inventive concept of the present application. The following is merely an example, where the lithium negative electrode sheet 2 also includes a negative current collector, a negative conductive agent, and a negative binder.
[0105] In the present application, the negative electrode current collector may be a metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector may be a copper foil, a carbon-coated copper foil or a stainless steel sheet.
[0106] In some embodiments, the shape of the negative electrode collector includes any one of a foil shape, a plate shape or a grid shape; further, the negative electrode collector includes any one of aluminum, copper, nickel or zinc; optionally, the negative electrode collector is a copper element, such as copper foil; further, the negative electrode collector includes any one of aluminum, copper, nickel or zinc alloy.
[0107] In some embodiments, the negative electrode conductive agent includes, but is not limited to, carbon-based materials, powdered nickel or other metal particles or conductive polymers. Carbon-based materials may include, for example, particles of carbon black, graphite, super-P, acetylene black (such as KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly (3,4-ethylenedioxythiophene) polystyrene sulfonate, and the like.
[0108] In some embodiments, the negative electrode binder includes, but is not limited to, one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polyoxymethylene (POM), polycarbonate (PC), polyamide (PA), acrylic plastics, other polyolefins and copolymers thereof, polysulfone, polyphenylene oxide (PPO) and carboxymethyl cellulose (CMC). Further, the negative electrode binder is polytetrafluoroethylene (PTFE) or polyvinylidene fluoride (PVDF).
[0109] It can be understood that the above-mentioned materials for positive electrode active material, positive electrode conductor, positive electrode binder, negative electrode conductor and negative electrode binder are merely illustrative examples, and any known positive electrode active material, positive electrode conductor, positive electrode binder, negative electrode conductor and negative electrode binder can be used in this application without violating the inventive concept of the present application.
[0110] The present application also provides a method for preparing a positive electrode sheet 1, which specifically comprises the following steps:
[0111] S1. Mixing the positive electrode active material, the positive electrode conductive agent and the positive electrode binder by jet milling, adding a solvent, and preparing a slurry;
[0112] S2. Coating the slurry on the surface of the aluminum foil current collector, drying it, forming an active layer on the surface of the aluminum foil current collector, and obtaining a positive electrode sheet 1.
[0113] The present application also provides a method for preparing a lithium negative electrode plate 2, the preparation method specifically comprising the following steps:
[0114] S11, mixing the particles of the negative electrode binder and the negative electrode conductive agent in a certain proportion by means of a jet mill, and calendering the mixture to obtain a functional film of a certain thickness;
[0115] S12, placing the functional film on the surface of the metal lithium foil and rolling it to obtain a negative electrode film;
[0116] S13, opening a receiving portion 21 on the surface of the negative electrode film by pulse laser etching technology to obtain a lithium negative electrode plate 2.
[0117] Specifically, the negative electrode film obtained in S12 can be obtained by multiple folding and rolling.
[0118] The pulse laser etching technology used in the present application can efficiently and accurately control the opening diameter, depth and bottom wall diameter of the accommodating portion 21 on the surface of the lithium negative electrode plate 2.
[0119] In other embodiments, the preparation method of the lithium negative electrode plate 2 can be directly laser etching on the surface of the lithium foil, thereby forming a receiving portion 21 on the surface of the lithium negative electrode plate 2, so that the receiving portion 21 has a preset opening diameter, depth and bottom wall diameter, etc.
[0120] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0121] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A lithium-ion solid-state battery, characterized in that: It comprises a positive electrode sheet, a lithium negative electrode sheet, and a solid electrolyte layer disposed between the positive electrode sheet and the lithium negative electrode sheet, wherein a receiving portion is disposed on the lithium negative electrode sheet, and the solid electrolyte layer is at least partially disposed in the receiving portion; the solid electrolyte layer comprises a binder base layer; wherein the cross section of the receiving portion is an arc, and the arc satisfies L=απr / 180, and α≤100°, r≤T, wherein L is the arc length, α is the center angle corresponding to the arc, r is the radius of the circle where the arc is located, and T is the thickness of the lithium negative electrode sheet; A solid electrolyte film is provided on the inner wall of the accommodation portion and / or the surface of the lithium negative electrode plate; The thickness of the solid electrolyte film is 1nm~100nm; The solid electrolyte film is a LiF film, a Li2O film, a LiPON film or a LiNiO2 film.
2. The lithium-ion solid-state battery according to claim 1, characterized in that: The opening diameter of the accommodation portion is d, the distance between any adjacent accommodation portions is D, and d / 2≤D≤2d.
3. The lithium-ion solid-state battery according to claim 1, characterized in that: The angle β between the tangent line at the endpoint of the arc and the plane of the lithium negative electrode plate is 5°~45°.
4. The lithium-ion solid-state battery according to claim 1, characterized in that: The inner wall of the accommodation portion and / or the surface of the lithium negative electrode plate are rough surfaces.
5. The lithium-ion solid-state battery according to claim 1, characterized in that: The inner wall of the accommodation portion and / or the surface of the lithium negative electrode plate forms a protruding structure, and the protruding structure is at least partially disposed in the solid electrolyte layer.
6. The lithium-ion solid-state battery according to claim 1, characterized in that: The thickness of the lithium negative electrode plate is 5um~300um.
7. The lithium-ion solid-state battery according to claim 1, characterized in that: The thickness of the solid electrolyte layer is 5um~100um.